Rating of perceived exertion in continuous sports: a scoping review with evidence gap map - Torres, Gonçalo; Maia, Filipe; Nakamura, Fábio Yuzo; Neiva, Henrique Pereira; Sousa, Ana (Frontiers in Sports and Active Living, 2025)
IntroductionRating of perceived exertion (RPE) is widely used for assessing training load in sports due to its validity, simplicity, and utility. Despite its broad application, the diverse contexts and methodologies in which it is used warrant a comprehensive review of the existing evidence.ObjectiveThis scoping review aims to map the current evidence on the use of RPE, focusing on its application, measurement methods, and reliability across different continuous sports.MethodsDatabases PubMed, SportDiscus (via EBSCO), Scopus, and Web of Science (core collection) were systematically searched until 22 May 2025 using the search terms: ([(RPE) OR (rating of perceived exertion) OR (Borg Scale)] AND (load) AND [(sports) OR (exercise) OR athletes]) Studies were included in this review if they complied with the following criteria: (1) conducted in continuous modes of exercise, (2) considering the comparison with other internal and external load measures, (3) when healthy and trained athletes were studied, (4) written in English language.ResultsA total of 234 studies involving 4,388 athletes were included in this review. Findings indicated that RPE is primarily used in training control and prescription (∼35%). A small number of studies focused directly on female athletes (∼7%), similarly master (∼1%) and elite athletes (∼13%) research was scarce.ConclusionThe findings suggest that although RPE is a valuable tool, variability in application across different exercise settings highlights the necessity to standardize its guidelines. Future research should focus on assessing the use of RPE in under-represented continuous sports.Systematic Review Registrationhttps://doi.org/10.17605/OSF.IO/C9PW6.